A new machine learning tool for mining brain stroke data - Mroczek, Teresa; Grzymala-Busse, Jerzy W; Hippe, Zdzislaw S (3rd International Conference on Human System Interaction, 2010)
This paper contains a brief description of a new computer programming tool for supervised machine learning, designed to generate production rules from data. The research tool described - named NGTS - was used for prediction of the Glasgow Outcome Scale and Rankin Scale for patients affected by severe brain damage.